Orientalisme dan Tantangan Pembentukan Identitas Nasional dalam Pembelajaran Sejarah - Mutiara Gita Cahyani; Suryo Ediyono (Historia Pedagogia, 2026)
This research aims to be able to see and analyze how Edward Said's criticism of Orientalism can affect how the challenge of forming the nation's national identity is especially in students in the midst of rapid development. Edward Said's Orientalist thought provides an opening for curriculum makers and historians to deconstruct and decolonize historical narratives that still have orientalist biases in them to become an emancipatory narrative in the goal of forming national identity. This research is based on a qualitative descriptive method, accompanied by a literature review method. In conclusion, with the existence of orientalist thinking and the challenges that exist in the goal of forming national identity in history learning, through the strategy of changing the curriculum and revitalizing the curriculum with the integration of local wisdom that provides equal opportunities to sources from various perspectives including local perspectives, so that the national identity that is built will become stronger, inclusive, and plural because of the accepted narrative of historical learning is based on the recognition of the diversity of the Indonesian nation itself.